Transection of the Nasal Base Muscles for the Correction of Plunging Tip: An Outcome Analysis. (26th April 2018) - Bayramiçli, Mehmet; Doğan, Zeynep Akdeniz
Abstract: Background: The plunging-tip deformity has been attributed to the combined actions of nasal base muscles. However, there are no quantitative data in the literature to discuss the effect of muscle transections on the clinical outcome. Objectives: This study was designed to assess the actions of the nasal tip, nasal base, and upper lip in patients with plunging-tip deformity and to compare their preoperative and postoperative activities following multiple myotomies. Methods: Patients were treated for nasal base animation deformity by the transection of the depressor septi nasalis, myrtiformis, nasalis, and levator labii superior alaeque nasi muscles. The profile views of preoperative and 12 months postoperative photographs were selected for measurements. Rest and smile images were overlaid to achieve alignment, and movements were measured with reference to the Frankfurt horizontal plane. Results: Twenty-seven (27) patients were included in the study. Movements of the nasal tip and nasal base were significantly reduced postoperatively. The upper lip shortened significantly in smile poses postoperatively compared with preoperative measurements. The change in the tip angle during animation significantly decreased in the postoperative measurements. Conclusions: Movements of the nasal tip and the alar base contributed significantly to the hyperdynamic nasal tip deformity. Transection of the nasal base muscles is an effective treatment method with a weaker recovery of the muscle function in the long term. Dynamic upper lip shortening is an unexpected finding following surgery and should be investigated further. Level of Evidence: 4: